Aufbau der Eisenskulptur von Georgina Beier an der Universität von Ife - Beier, Ulli (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Photographs; Sculpture; Artists; Women artists; Ile-Ife; Iron Sculpture; Nigeria